Development of Children with Mental Disorders through Islamic Religious Education and Medical Approaches - Ju’subaidi, Ju’subaidi; Mahmudin, Afif Syaiful (IAIN Ponorogo, 2023)
Mental disorders occur in Ponorogo, precisely in Paringan village, Jenangan. Based on researchers' observations, it was known that the number of mental disorders sufferers was 60 people, from children to adults. In Paringan village, a Mental Health Assistance Health Center was established in 2011. Some efforts dealing with mental disorders include promotion or prevention, curative (treatment), and rehabilitation. These three were implemented in the family, institution, and community environment. For psychiatry, it was done as early as possible, repeatedly and consistently, to be realized in life in the future. The research method used is qualitative, with a case study approach in Paringan Mental Health Support Health Center. Based on an analysis of various findings in the field, the researchers found that the Islamic Religious Education approach model for children with mental disorders was carried out by looking at the causes of children's mental disorders and the treatment and rehabilitation processes children received. It would become a reference for the next step, then determine and develop various forms of religious development activities under the conditions and characteristics of the child. Medical treatments in the coaching process would accompany them because this coaching was not a preventive but a corrective and preservative effort against mental disorders.